From colonial legacy to contemporary reality: attitudes towards English and Hindi hegemony in India - Sadaf Khan; Thapasya Jayaraj (Humanities & Social Sciences Communications)
Abstract The dominance of one powerful, ‘killer’ language, particularly in formerly colonized countries, has been studied mainly in the context of language education in a multilingual scenario. However, attitudes towards linguistic hegemony remain largely unexplored, an issue that takes on added significance in India, a country known for its exceptional linguistic diversity. The ethnographic study attempts to bridge the gap by analyzing the implicit and explicit language attitudes toward English and Hindi language hegemony among Indians representing a diverse spectrum of linguistic, geographical, and socioeconomic backgrounds. Explicit attitudes, consciously held and reported perceptions, were investigated through one-on-one and group interviews with 60 participants while implicit attitudes, unconsciously held beliefs, were explored through field observations. The study also examined whether English is still viewed as a remnant of colonialism in India. The findings of the thematic analysis reveal that English has largely shed its colonial associations, with socioeconomic status, and the medium of instruction significantly influencing these attitudes. With its exploration of Hindi hegemony in addition to English, the research offers fresh insights into the evolving linguistic landscape of India and contributes to a more nuanced understanding of language dynamics in a post-colonial, globalized society.